E-Trust Mediating E-Service Quality and Online Purchase Decision in Digital Intercity Transportation - Eveline Nathalie A. Sitohang; Budi Prasetiyo (Penerbit Goodwood, 2026)
Purpose: This study addresses the gap between digital investment and declining online sales at Primajasa company. It evaluates how E-Service Quality affects Online Purchase Decisions through the mediating role of e-trust among university students. Research Methodology: A quantitative causal approach was used to gather data from 268 Telkom University students who used Primajasa’s digital website. The structural model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 3.0 software. Results: The analysis revealed that E-Service Quality is a strong predictor of e-trust (? = 0.880, p = 0.000), which subsequently drives Online Purchase Decisions (? = 0.735, p = 0.000). Because the direct link between service quality and purchase behavior is statistically insignificant (? = 0.195, p = 0.131), this study confirms that e-trust acts as a total mediator (? = 0.647, p = 0.000). Conclusions: Perceived trust is the primary mechanism that transforms service quality into actual transaction. Digital transport providers must prioritize trust-building strategies to ensure successful adoption by users. Limitations: The sample was restricted to students from one institution on a single route, excluding potential moderators such as perceived risk and price sensitivity. Contributions: As one of the few studies focusing on Indonesia's intercity transport, this study validates the essential role of e-trust in driving digital conversion rates.